The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/c9ra08090b
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the metabolic biomarkers and pathway changes in crucian under carbonate alkalinity exposure using high-throughput metabolomics analysis based on UPLC-ESI-QTOF-MS

Abstract: We explore the metabolic biomarker and pathway changes accompanying the adaptive evolution of crucian subjected to carbonate alkalinity exposure, using UPLC-ESI-QTOF-MS, in order to understand the molecular physiological mechanisms of saline–alkali tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…After using the Pareto method to standardize the data, it was determined that some metabolic pathways in the blood involved in phenylalanine, tyrosine and tryptophan biosyntheses, phenylalanine metabolism, valine, leucine, and isoleucine biosyntheses, sulfur metabolism, tricarboxylic acid (TCA) cycle, and nicotinate and nicotinamide metabolism were associated with the cardiovascular toxicity effect of acrylamide. The metabolic pathway influence values are listed in Table S1, where a metabolic pathway with an influence value greater than or equal to 0.1 can be selected as a potential key metabolic pathway for acrylamide toxicity …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After using the Pareto method to standardize the data, it was determined that some metabolic pathways in the blood involved in phenylalanine, tyrosine and tryptophan biosyntheses, phenylalanine metabolism, valine, leucine, and isoleucine biosyntheses, sulfur metabolism, tricarboxylic acid (TCA) cycle, and nicotinate and nicotinamide metabolism were associated with the cardiovascular toxicity effect of acrylamide. The metabolic pathway influence values are listed in Table S1, where a metabolic pathway with an influence value greater than or equal to 0.1 can be selected as a potential key metabolic pathway for acrylamide toxicity …”
Section: Resultsmentioning
confidence: 99%
“…The metabolic pathway influence values are listed in Table S1, where a metabolic pathway with an influence value greater than or equal to 0.1 can be selected as a potential key metabolic pathway for acrylamide toxicity. 25…”
Section: Analysis Of Metabolic Pathwaysmentioning
confidence: 99%
“…It has been widely applied in unraveling underlying mechanisms of physiological processes and abiotic stress responses in aquatic organisms [ 23 ]. Previous studies have reported the metabolic variation characteristics of the crucian carp gill and liver in response to saline-alkali stress by using metabolomics technology [ 21 , 24 , 25 ]. However, there is little information concerning the mechanism underlying the carbonate alkaline stress-induced toxic effects and changes in metabolic profile.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used to study the abstruse metabolic mechanisms of fish in response to changes in endogenous and exogenous factors [ 17 ]. Sun et al [ 18 ] utilized UPLC-QTOF/MS metabolomics technology to explore the changes in biomarkers and pathways of crucian carp ( Carassius auratus ) under carbonate alkalinity exposure to reveal the molecular and physiological mechanisms of fish salt tolerance. Ladisa et al [ 19 ] employed UHPLC-MS technology to investigate the seasonal metabolic changes and energy distribution associated with the growth and reproductive stages of the liver of male goldfish ( Carassius auratus ).…”
Section: Introductionmentioning
confidence: 99%